The impact of obesity on walking and physical performance - Manal K Youssef (SpringerOpen, 2014)
Background Obesity-induced limitations of the cardiopulmonary and the metabolic systems, resulting in exertional dyspnea, contribute to the limitations in the functional capacity frequently observed in obese individuals. In addition, the sedentary lifestyle often adopted by these individuals further compounds and contributes to impaired exercise tolerance. Aim of the study The current study was conducted to detect the effect of lifestyle modification in the form of weight reduction by diet and aerobic exercise on walking and physical performance. Patients and methods Twenty obese participants were included in this study. Their ages ranged from 25 to 43 years. All participants were evaluated before the first session of physical therapy program and at the end of the program after 2 months of exercise and a low-caloric diet of 25 kcal/kg actual weight/day through physical evaluation, which included anthropometric measurements, BMI, inspiratory capacity, and a physical performance test, which includes four tests (15-m rapid walking test, a timed up-and-go test, and stair climbing and stair descending tests). Results Analysis of data revealed significant improvement in the parameters assessed as follows: weight decreased from 81.3 ± 8.5 to 68.00 ± 4.50 kg (P ≤ 0.001); BMI decreased from 29.8 ± 2.0 to 24.1 ± 2.0 kg/m 2 (P ≤ 0.001); waist circumference decreased from 120.3 ± 14.4 to 112.3 ± 9.6 cm (P = 0.053); hip circumference decreased from 121.3 ± 6.1 to 112.6 ± 11.4 cm (P = 0.009); inspiratory capacity increased from 14.4 ± 2.7 to 21.0 ± 2.3 s (P ≤ 0.001); time of 15 m walk decreased from 21.2 ± 1.7 to 15.5 ± 2.1 s; timed up-and-go test decreased from 24.1 ± 2.8 to 15.3 ± 2.3 s; stair climbing time decreased from 45.3 ± 6.5 to 34.2 ± 2.6 s; stair descending time decreased from 36.2 ± 2.3 to 27.2 ± 2.1 s. Hence, the total physical performance increased from 31.9 ± 10.3 to 23.0 ± 8.5 s (P ≤ 0.001) and consequently improved the quality of life. Conclusion Lifestyle modification in the form of a low-caloric diet accompanied by exercise has a positive effect on physical performance and consequently on the quality of life.